2015
DOI: 10.1590/s1984-29612015020
|View full text |Cite
|
Sign up to set email alerts
|

Amblyomma nodosum (Neumann, 1899): observations on life cycle under laboratory conditions

Abstract: The natural hosts of Amblyomma nodosum in the immature stages are a variety of birds and the anteater in the adult stage. However, so far no data have been published about this tick's life cycle. To fill this gap, a record was made of its development under laboratory conditions. All the procedures were controlled in a BOD chamber set at 27±1 °C and 80±10% relative humidity and scotophase. The parasitic stages were raised on rabbits (Oryctolagus cuniculus Linnaeus, 1758), from which more than 50% of larvae and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…This is the first report of Rickettsia sp. strain NOD in Goiás, and it is possible that A. nodosum is involved in enzootic cycles of this rickettsia in preserved forest areas (Ogrzewalska et al ., ; Pinheiro et al ., ), such as those that occur in Trindade municipality, which highlights the danger of the presence of potentially pathogenic rickettsia in this area.…”
Section: Discussionmentioning
confidence: 96%
“…This is the first report of Rickettsia sp. strain NOD in Goiás, and it is possible that A. nodosum is involved in enzootic cycles of this rickettsia in preserved forest areas (Ogrzewalska et al ., ; Pinheiro et al ., ), such as those that occur in Trindade municipality, which highlights the danger of the presence of potentially pathogenic rickettsia in this area.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that, under laboratory conditions, A. nodosum exhibit a high degree of dependence on their hosts and environment for development ( Pinheiro et al, 2015 ). Although the records of unexpected parasitism by this tick species is considered incidental, there could be a potential relation between the selection of a host by this tick species and various ecological features, such as habitat specificity, host availability, and type of cycle of the ticks and environmental conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the fact that anteaters are the natural host of A. nodosum in the adult stage, while a variety of birds are hosts of its immature stages (Barros-Battesti et al, 2006). A. nodosum has been found to be highly dependent on its hosts and environment (Pinheiro et al, 2015). Amblyomma humerale, another important species of the genus Amblyomma, is considered endemic to South America, where it has been mainly described parasitizing land tortoises, including reports in Rondônia (Labruna et al, 2002).…”
mentioning
confidence: 99%